IMPLEMENTASI NILAI-NILAI MODERASI BERAGAMA: STUDI EVALUATIF MODEL CIPP PADA SISWA SMA NEGERI KOTA SINGKAWANG - Prisuna, Bayu Fitra; Asmiati; Prisuna, Mega Armeilita (Institut Agama Islam Negeri Kendari, 2026)
This study aims to analyze the implementation of religious moderation values in public senior high schools in Singkawang City using the CIPP (Context, Input, Process, Product) evaluation model. The study employed a quantitative approach with an evaluative survey design involving 315 12th-grade students selected through disproportionate stratified sampling. Data were collected through structured questionnaires and documentation, then analyzed using descriptive statistics. The results showed that the implementation of religious moderation was generally in the good category across all evaluation dimensions. Schools have normative readiness and program relevance in a multicultural context, while input components such as educators, teaching materials, facilities, and parental involvement are available although not yet fully integrated systemically. In terms of process, internalization of values occurs through relatively conducive learning and social interactions with the active role of teachers as agents of moderation. In terms of product, the program has a positive impact on increasing tolerance, mutual respect, and students' ability to apply the values of moderation in everyday life. However, institutional strengthening and policy integration are still needed to ensure the sustainability and systematic transformation of school culture.